Investigating the inflation-output-nexus for the euro area: Old questions and new results - Dieter Gerdesmeier; Hans-Eggert Reimers; Barbara Roffia (Hochschule Wismar, Fakultät für Wirtschaftswissenschaften, 2023)
The relationship between inflation and real GDP growth is one of the most widely researched topics in macroeconomics. At the same time, it is certainly not exaggerated to claim that this nexus also stands at the heart of monetary policy, given the fact that low inflation in combination with high and sustained output growth should be the central objective of any sound economic policy. The latter notion becomes even more obvious, when taking account of the fact that many central banks all over the world have selected target levels for inflation and communicated them to the public. Against this background, it is of utmost importance for central banks to know more about the nature and form of the relationship between inflation and real GDP. This study tries to shed more light on the concrete shape of this relationship for the euro area and, more specifically, on the issue of possible regime shifts therein. The analysis provides strong evidence for non-linear effects in the euro area. As a by-product, the methods used allow for a quantification of the point of switch across the different regimes and it is found that this breakpoint closely matches the ECB's previous definitions of price stability and its new inflation target of 2%. While these results look encouraging, further research in this area seems warranted.
Keywords: E31; E52; E58; 330